Induksi Teknologi Pompa Venturi dan Protein Skimmer dalam Budidaya Udang Vaname (Litopenaeus Vannamei) - Pramudia, Zulkisam; Fuad, Fuad; Prayogo, Tribudi; Anggayasti, Wresti Listu; Salamah, Lutfi Nimatus; Risqiana, Mega Asri (Penerbit Goodwood, 2025)
Purpose: This community service initiative introduces an innovative solution combining venturi pump system technology and protein skimmer to enhance water quality, production efficiency, and sustainability in round tank-based white shrimp farming. The protein skimmer helps reduce dissolved organic matter and supports the maintenance of dissolved oxygen (DO) levels, both essential for shrimp survival. Methodology/approach: The approach includes participatory planning, Focus Group Discussions, the induction of venturi aerator and protein skimmer combination, socialization and technical training, technology demonstration (including water quality monitoring), partner assistance, and continuous monitoring and evaluation. The implementation partner is CV Nusantara Agro Mandiri, located in Tuban. Results/findings: The technology application led to an average increase in DO by 3 mg/L due to the venturi pump, and a reduction of total dissolved solids (TDS) by 400 mg/L with the help of the protein skimmer. These improvements supported better shrimp growth, with an average daily weight gain of 0.1 grams. Conclusion: Integrating venturi pump and protein skimmer technologies provides an effective means to improve water quality and enhance shrimp growth in round tank systems. This contributes to more stable and sustainable aquaculture environments. Limitations: Wider-scale implementation is required to test the technology under more diverse environmental and water quality conditions. Cost efficiency remains a key concern for broader adoption by farmers. Contribution: This technological combination offers a valuable strategy for improving cultivation environments and enhancing the productivity. Contribution to SDGs: This initiative supports SDG 2: Zero Hunger, SDG 14: Life Below Water, and SDG 17: Partnerships for the Goals.